Phosphoinositide-signaling is one component of a robust plant defense response - Hung, Chiu-Yueh; Aspesi Jr, Peter; Hunter, Melissa R.; Lomax, Aaron W.; Perera, Imara Y. (Frontiers in Plant Science, 2014)
The phosphoinositide pathway and inositol-1,4,5-triphosphate (InsP3) have been implicated in plant responses to many abiotic stresses; however, their role in response to biotic stress is not well characterized. In the current study, we show that both basal defense and systemic acquired resistance responses are affected in transgenic plants constitutively expressing the human type I inositol polyphosphate 5-phosphatase (InsP 5-ptase) which have greatly reduced InsP3 levels. Flagellin induced Ca2+-release as well as the expressions of some flg22 responsive genes were attenuated in the InsP 5-ptase plants. Furthermore, the InsP 5-ptase plants were more susceptible to virulent and avirulent strains of Pseudomonas syringae pv. tomato (Pst) DC3000. The InsP 5-ptase plants had lower basal salicylic acid (SA) levels and the induction of SAR in systemic leaves was reduced and delayed. Reciprocal exudate experiments showed that although the InsP 5-ptase plants produced equally effective molecules that could trigger PR-1 gene expression in wild type plants, exudates collected from either wild type or InsP 5-ptase plants triggered less PR-1 gene expression in InsP 5-ptase plants. Additionally, expression profiles indicated that several defense genes including PR-1, PR-2, PR-5, and AIG1 were basally down regulated in the InsP 5-ptase plants compared with wild type. Upon pathogen attack, expression of these genes was either not induced or showed delayed induction in systemic leaves. Our study shows that phosphoinositide signaling is one component of the plant defense network and is involved in both basal and systemic responses. The dampening of InsP3-mediated signaling affects Ca2+ release, modulates defense gene expression and compromises plant defense responses.